Microbial Contamination on Kitchen Surfaces in University Student Housing: Insights from Swab Analysis and Behavioral Surveys - Viana, Gustavo Guimarães Fernandes [UNESP]; Mello, Ana Julia Pereira [UNESP]; Apresentação, Beatriz da [UNESP]; Gonçalves, Danilo Dos Santos [UNESP]; Gerolamo, Eduarda Yamauti [UNESP]; de Castro, Giulya Monteiro [UNESP]; da Silva, Guilherme Cardoso [UNESP]; Corá, Henrique de Rezende [UNESP]; da Silva Marcelino, Izabella Regina [UNESP]; Busch, Kaedra Piva [UNESP]; Aguiar, Luana Kleinubing [UNESP]; Mendonça, Luiza Mattos [UNESP]; et al. (Elsevier, 2025)
Shared kitchens are potential hotspots for microbial contamination due to frequent use and poor hygiene. In student residences, these risks are heightened by diverse hygiene behaviors and limited oversight. This study aimed to evaluate microbial contamination and hygiene-related behaviors in university student residences. Thirty student households in Botucatu, Brazil, were investigated through microbiological sampling of kitchen surfaces (refrigerator, sink, dish towels, and sponge). Samples were analyzed to assess the counts of mesophilic aerobic bacteria and Enterobacteriaceae, and the detection of Salmonella spp. and L. monocytogenes. In addition, a structured questionnaire was applied to gather data on hygiene routines and food handling practices. Feedback sessions were held to communicate the results to each household. No samples tested positive for Salmonella spp. or L. monocytogenes. Sponges exhibited the highest levels of microbial contamination, with median counts of 8.63 log CFU/cm2 for mesophiles and 5.72 log CFU/cm2 for Enterobacteriaceae, followed by dish towels (4.11 and 3.60 log CFU/cm2), sinks (1.27 and 0.24 log CFU/cm2), and refrigerators (-0.25 and -0.18 log CFU/cm2). Some associations between hygiene behaviors and microbial load were observed, including differences linked to dishwashing habits and the number of residents using the refrigerator. The descriptive trends suggest that certain behaviors, such as the frequency of dish towel sanitization and refrigerator cleaning, may influence microbial risks. These findings emphasize the importance of consistent hygiene practices in shared kitchen environments and support the development of educational and preventive strategies aimed at improving food safety among young adults living in communal housing, such as promoting proper dish towel and sponge replacement, clear cleaning responsibilities, and separation of utensils for raw and cooked foods.